Assessment of the Lattice Discrete Element Method in the simulation of wave propagation in inhomogeneous linearly elastic geologic materials. Issue 151 (December 2021) - Iturrioz, Ignacio; Riera, Jorge D.
Abstract: Attenuation equations for seismic peak ground acceleration, ground velocity or seismic response spectra, in terms of distance to the source and magnitude of the causative event are typically based on results of the theory of linearly elastic wave propagation in homogenous solids. The latter also furnishes the fundaments for both the study of vibrations induced by surface loadings on the ground and for the design of isolation systems. In engineering applications, the propagation of seismic waves through inhomogeneous materials acquires unquestionable relevance. At the same time, analytical solutions impose increasing difficulties, requiring resort to numerical approaches. In the paper, a version of the Discrete Element Method, herein designated as Lattice Element Method (LDEM), is employed to study propagation of body waves in linearly elastic homogeneous and inhomogeneous media, with or without viscous linear material damping, with the objective of assessing bounds for solutions based on the assumption of linear elastic material models. Highlights: The Discrete Element Method has been shown to be efficient in the solution of problems involving fracture and inhomogeneous materials. Applications of DEM models to predict the seismic isolation systems still require a thorough evaluation of the numerical approach. The performance of DEM models to predict seismic waves propagation through geologic media is assessed in the paper. One difficulty encountered is the scarcity of theoretical Continuum Mechanics wave propagation solutions for inhomogeneous media.